Hepatocyte fate upon TGF-β challenge is determined by the matrix environment - Meyer, Christoph; Liebe, Roman; Breitkopf-Heinlein, Katja; Müller, Alexandra; Weng, Honglei; Ebert, Matthias; Dooley, Steven (Differentiation, 2015)
Primary hepatocytes are a versatile tool to investigate all aspects of liver function, and frequently used in drug development and testing. Upon TGF-β challenge, hepatocytes either undergo an epithelial to mesenchymal transition (EMT) or apoptosis: culture on stiff collagen (monolayer) results in EMT whereas hepatocytes in a soft collagen matrix (sandwich) undergo programmed cell death. In this study, we analyzed the transcriptional programs triggered by TGF-β under different culture conditions. Our results indicate that TGF-β initiates an identical transcription profile in hepatocytes irrespective of the cellular environment. The fact that we nevertheless observe two vastly different phenotypes indicates that the matrix environment rather than the TGF-β induced expression signature is the major determinant of the hepatocellular response. To confirm the impact of the surrounding matrix environment on the hepatocytes׳ phenotype in response to TGF-β signaling, we studied the effect of Snail overexpression and knockout in both culture conditions. Neither genetic manipulation showed an impact on hepatocytes’ fate upon TGF-β treatment, confirming the crucial role of the surrounding matrix. Our findings provide novel insights into the hepatocellular basis of the fate decision between EMT and apoptotic cell death, and might explain why liver cells can react in very different manners to identical stimuli when tissue remodeling has changed the matrix environment, as occurs in a fibrotic liver.